Ethanolic extract of Garcinia cowa leaves reduces adipocyte size and hepatic fat accumulation in high-fat diet-fed rats - Siwaporn Praman, Wannisa Sukhorum, Thidarat Duangyod, Rawiwan Charoensup (Journal of Applied Pharmaceutical Science, 2025)
Garcinia cowa Roxb. ex Choisy (G. cowa) has traditionally been used to enhance blood circulation, aid digestion, and act as an antipyretic and expectorant. Although previous studies have demonstrated its anti-hyperlipidemic activity in vitro, the anti-obesity effects of G. cowa remain inadequately explored. This study evaluates the effects of ethanolic G. cowa leaf extract (GCE) in high-fat diet (HFD)-induced obese rats. Wistar rats were divided into four groups: normal diet, HFD, HFD with GCE (200 mg/kg), and HFD with GCE (400 mg/kg), treated for 8 weeks. HFD significantly increased body weight, fat mass, and feed efficiency ratio, whereas GCE supplementation attenuated these effects without affecting food intake. In addition, histological analysis revealed HFD-induced adipocyte enlargement and hepatic fat accumulation. Notably, the administration of GCE restored both adipocyte size and number while also reducing hepatic fat accumulation. However, among groups, no significant differences were observed in liver and kidney weights, serum lipid profiles, liver enzymes, or blood glucose. Hydroxycitric acid and flavonoids may contribute to the anti-obesity effects of GCE. These findings suggest that GCE treatment reduced adipocyte size and hepatic lipid accumulation in HFD-induced obese rats, demonstrating its potential anti-obesity properties.
Keywords: Garcinia cowa, anti-obesity, high-fat diet, adipose tissue, hepatic fat accumulation